2015
DOI: 10.1111/aos.12728
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of parafoveal cone density in patients taking hydroxychloroquine in the absence of clinically documented retinal toxicity

Abstract: ABSTRACT.Purpose: To measure cone density in patients taking hydroxychloroquine (HCQ), with no clinical evidence of maculopathy. Methods: Patients visiting for HCQ macular toxicity screening in the Besanc ßon University Hospital Ophthalmology Department (France) were studied. They underwent routine examination including spectral-domain optical coherence tomography, fundus autofluorescence and multifocal electroretinogram to detect HCQ-induced retinal toxicity. Cone metrics (density, spacing and percentage of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…As Stepien et al showed, there is some dropout in cone count as well as a simultaneous increase in cone spacing through the use of adaptive optics in HCQ retinopathy at a preclinical stage [13]. Similar results were confirmed by a following study [14].…”
Section: Discussionsupporting
confidence: 61%
“…As Stepien et al showed, there is some dropout in cone count as well as a simultaneous increase in cone spacing through the use of adaptive optics in HCQ retinopathy at a preclinical stage [13]. Similar results were confirmed by a following study [14].…”
Section: Discussionsupporting
confidence: 61%
“…For example, Chew et al have reported exclusion of approximately 40% of images due to image quality in their analyzed data set 16 . Debellemaniere et al had to exclude at least one eye from 46.9% of subjects due to poor AO image quality in their study of patients taking hydroxychloroquine without any evidence of maculopathy 34 . Furthermore, Feng et al reported that in their study of AO-FIO images of healthy subjects aged 14 to 69, the images from 52.7% were excluded due to image quality 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The proportions of sampling windows that were discarded before analysis due to poor image quality were 43% when taken from single AO image frames, and 40% when taken from the wide-field AO montages. Debellemanière et al 11 reported exclusion of at least one eye from 46.9% of subjects due to inadequate AO image quality in their study of patients taking hydroxychloroquine without any evidence of maculopathy. Further, in a separate study of AO images obtained from 72 eyes of healthy subjects aged 14 to 69 years, the images from 52.7% of subjects were excluded from analysis due to image quality that was insufficient to allow automatic montage and/or cone counting, including two patients who were aged under 30 with no apparent ocular pathology.…”
Section: Discussionmentioning
confidence: 99%